Machining Performance of AA2024/5Al2O3/5Gr Hybrid Composites under Al2O3 Mixed Dielectric Medium - Nandagopal Kaliappan; M. Balaji; T. CH Anil Kumar; Haqqani Arshad; N. B. Prakash Tiruveedula; S. Hemavathi; Kibebe Sahile (International Journal of Chemical Engineering)
In this research work, AA2024/5Al2O3/5Gr hybrid composites fabricated through stir casting were machined utilising an electric discharge machine (EDM). Experiments were performed by varying current, pulse on time (POT), gap voltage (GV), and Al2O3 powder concentration (PC). The experiments were designed using response surface methodology in which material removal rate (MRR), tool wear rate (TWR), and surface roughness (Ra) were recorded as responses. The addition of Al2O3 particles has a positive impact on MRR and Ra, whereas it has a negative impact on TWR. The interaction impact of process parameters (p-p) on responses was thoroughly analyzed using contour plots. A mathematical model was developed and validated for all the responses. The experimental results were compared with the predicted values. It was found that all the values have a maximum deviation of 3.5%. The ANOVA table reveals that the PC was the most influential factor followed by the current.